2011
DOI: 10.1016/j.bcp.2010.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of hepatic stellate cells mediated by specific protein nitration

Abstract: Inflammatory conditions are characterized by continuous overproduction of nitric oxide (NO) that can contribute to cell survival but also to cell demise by affecting apoptosis.These facts are important in regulation of hepatic fibrogenesis during exposure to inflammatory stress, since elevated NO may pose the risk of cells with a pro-fibrogenic phenotype giving rise to a sustained proliferation leading to chronic fibrosis. Since nitration of tyrosine residues occurs in a range of diseases involving inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…We conclude that Lyn is an emerging relevant target in anti-fibrotic therapeutic strategies, and the inhibition of Lyn kinase in stellate cells prevents the replacement of parenchyma with fibrotic tissue in pancreas. Since fibrotic process, which result from myofibroblast activation, can occur in many tissues within the body, the role of Lyn might be a general phenomenon and relevant in other tissues besides pancreas, as it was previously suggested by other authors (Pontrelli et al, 2006; Mòdol et al, 2011). Notably, reactive nitrogen species generated in inflammation can create nitrated biomolecules in various tissues and the role of tyrosine nitration in the mechanism of stable Lyn tyrosine kinase activation was previously reported in other tissues besides pancreas (Mallozzi et al, 2001).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We conclude that Lyn is an emerging relevant target in anti-fibrotic therapeutic strategies, and the inhibition of Lyn kinase in stellate cells prevents the replacement of parenchyma with fibrotic tissue in pancreas. Since fibrotic process, which result from myofibroblast activation, can occur in many tissues within the body, the role of Lyn might be a general phenomenon and relevant in other tissues besides pancreas, as it was previously suggested by other authors (Pontrelli et al, 2006; Mòdol et al, 2011). Notably, reactive nitrogen species generated in inflammation can create nitrated biomolecules in various tissues and the role of tyrosine nitration in the mechanism of stable Lyn tyrosine kinase activation was previously reported in other tissues besides pancreas (Mallozzi et al, 2001).…”
Section: Discussionmentioning
confidence: 71%
“…Lyn inhibition attenuates fibrosis in chronic allograft nephropathy models through prevention of plasminogen activator inhibitor-1 (PAI-1), a powerful pro-fibrotic mediator (Pontrelli et al, 2006). Another group suggested that Lyn nitration increases Syk activity and regulates hepatic stellate cell apoptosis in the course of chronic fibrosis of liver (Mòdol et al, 2011). Thus, the mechanisms and consequences are complex and variable.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, NO produced by infiltrated macrophages in inflamed regions could play an important role in controlling liver fibrosis by inducing apoptosis of both cell types, monocytes and HSC (Langer et al, 2008;Natal et al, 2008;Módol et al, 2011). Monocytes/macrophages can also modulate the turnover of extracellular matrix by producing metalloproteinases, such as MMP-9, in a process induced by cytokines like IL-1β and TNF-α (McCawley and Matrisian, 2001;Saren et al, 1996;Kusubata et al, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…3-NT is routinely used as a biomarker for protein damage that is induced by oxidative inflammation [83]. Continual overproduction of nitric oxide or NO is a classical marker of the cellular inflammation, and this overproduced NO not only can damage the organelles but is also a contributing factor for cell death mainly by mediating apoptosis [84]. Nitrative controlled apoptosis in hepatic stellate cells (HSCs) is crucial because protein nitration plays a significant role in liver fibrosis prognosis [84].…”
Section: Nitrationmentioning
confidence: 99%